ANALYZE HOW CHARACTERS ARE DEVELOPED IN DRAMA, INCLUDING THEIR MOTIVATIONS, CONFLICTS, AND RELATIONSHIPS - Jabbar Xojanov; Aldanazarova Gulmira (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: This paper examines the development of characters in drama, focusing on their motivations, conflicts, and relationships. Characters in drama are driven by their internal and external motivations, which propel their actions and shape their behavior. Through conflicts, both internal and external, characters confront challenges and obstacles that force them to evolve and grow over the course of the story. Additionally, characters' relationships with others play a crucial role in their development, offering insights into their personalities, values, and beliefs. By analyzing how characters are developed in drama, we gain a deeper understanding of the complexities of human nature and the dynamics of storytelling on stage.